Implementasi Teknologi Pengenalan Wajah Untuk Login Website Chic Glasses Berbasis Convolutional Neural Network(CNN) - Yunita, Farida; Irwanto, Irwanto; Winanto, Andri; Nuranisa, Angelita Nova; Nurhayati, Setia; Araffi, Dimas Ilham (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
The research discussed the development of a face recognition technology for the login system of an e-commerce website. The study's main focus was enhancing the security and efficiency of online transactions through the use of biometric identification systems. The researchers implemented a Face Recognition Login Website using a CNN, known for its ability to extract features and classify faces effectively. The research involved various stages, such as data collection through a web camera, data pre-processing, and the design of a CNN architecture with feature learning and classification layers. By deploying this CNN-based facial recognition technology on e-commerce websites, the researchers expect to add an extra layer of security, boost user trust, and offer a safer and more convenient online transaction experience.